Giving Foot Soak Therapy Using Warm Water To Reduce Blood Pressure In Elderly Hypertension In Inpatient Room of Hospital X (Comprehensive Health Care, 2024)
Background: Hypertension is often referred to as the Silent Killer and most people with hypertension are never aware of the signs and symptoms. And for this reason it is very important that blood pressure must be measured regularly. Objective: To be able to understand, explain and apply evidence-based practices in professional nursing, after carrying out Foot Soak Therapy Using Warm Water to Reduce Blood Pressure in Hypertensive Elderly in the Inpatient Room of X Hospital Research Method: Evidence base nurse (EBN) design used is the Quasy Experiment, especially the pretest-posttest design. Namely by conducting observations before and after the intervention without a control group. There were two intervention groups, namely the group that was given foot soak therapy using warm water for 4 consecutive days and carried out2 times a day. Results: The results show that after the intervention the blood pressure in elderly patients had a mean value of 1.75 (SD=0.500) while in the control group the mean blood pressure had a mean value of 1.50 (SD=0.577) with a p-value of 0.083 or greater than the significance value of p -value >0.05 Conclusion: which means there is no significant difference in mean blood pressure between the foot soaking intervention group using warm water and the control group in reducing blood pressure in the elderly in this study.